Higher Education Institutions Educational Process Digitalization in the Context of the Necessity to Provide a Model for Students' Choice of Training Areas and Academic Specialties - Kozorez, Dmitriy A.; Dolgova, Elena A.; Korneenkova, Anna V.; Rumakina, Alena V.; Sha, Minggong (International Journal of Criminology and Sociology, 2021)
The digital revolution in the Russian economy is leading to a radical change in the labour market, the emergence of new competencies, improved cooperation, increased responsibility of citizens, their ability to make independent decisions. This, in turn, is the reason for the reorganisation of the educational process, largely based on the use of IT technologies. The purpose of the paper is to solve the problem of unification of educational programmes within the framework of digitalisation of the educational process in universities. The unification of educational programmes is proposed, which ensures the conducting of the educational process without losing its quality, taking into account individual educational trajectories, as well as implementing a model for students' choice of a direction or training specialty, starting from the third year of study, and, as a result, making it possible to transfer students between educational levels up to 5 semesters, and within a level - up to 6 semesters. The unification of educational programmes is considered on the example of the Moscow Aviation Institute (National Research University). The proposed unification covers the extended groups of specialties taking into account different levels and forms of training, as well as various territorial sites (branches).